Relationship Between Acute Benzodiazepine Poisoning and Acute Pancreatitis Risk: A Population-Based Cohort Study. Issue 52 (December 2015) - Liaw, Geng-Wang; Hung, Dong-Zong; Chen, Wei-Kung; Lin, Cheng-Li; Lin, I-Ching; Kao, Chia-Hung
Abstract : Abstract: We designed a population-based retrospective cohort study to investigate the association between the event of benzodiazepine (BZD) poisoning and the risk of acute pancreatitis. In the present study, 12, 893 patients with BZD poisoning during 2000 to 2011 were enrolled and matched with 4 comparison patients according to mean age and sex. We determined the cumulative incidences and adjusted hazard ratios of acute pancreatitis. A significant association was observed between BZD poisoning and acute pancreatitis. After adjustment for potential risk factors, the patients with BZD poisoning had a 5.33-fold increased risk of acute pancreatitis compared with the controls without BZD poisoning (HR = 5.33, 95% CI = 2.26–12.60). The results revealed that acute pancreatitis in patients with BZD poisoning occurred in a follow-up time of ≤1 month (HR = 50.0, P < .001), and the risk of acute pancreatitis was no different between the patients with and without BZD poisoning when the follow-up time was >1 month (HR = 1.07, P > .05). This population-based study revealed the positive correlation between the event of BZD poisoning and an increased risk of acute pancreatitis. The findings warrant further large-scale and in-depth investigation.